PENGARUH KOMPENSASI FINANSIAL DAN NONFINANSIAL TERHADAP KINERJA KARYAWAN PADA PUTRA BARU SWALAYAN CABANG KUTOWINANGUN - Wahyuningsih, Intan; Siharis, Alkadri Kusalendra (Transpublika Publisher, 2022)
Employee performance is an important factor for the company in achieving its goals. Performance is the result of work in quality and quantity that has been achieved by employees in completing tasks according to their responsibilities. This study aims to determine the effect of financial and non-financial compensation on employee performance at Putra Baru Swalayan Kutowinangun Branch. This study uses primary data sourced from direct research by distributing questionnaires to respondents and using multiple linear regression analysis tools. This study shows that financial and non-financial compensation has a significant influence on employee performance. It can be concluded that the provision of compensation will improve employee performance.